Social and solidarity economy initiatives in circular economy: the case of second-hand clothing in Greece - Paraschi, Dionysia Evgenia; Arvanitidis, Paschalis (International Conference on Business and Economics - Hellenic Open University, 2023)
Mainstream approaches to circular economy focus on the economic and the environmental dimensions disregarding the social element of sustainable development. Proper integration of the social dimension requires the adoption of a different consumption culture and of economic behavior in general, all of which fall within the mentality of the social and solidarity economy. This perspective places due attention to social responsibility (articulated through cooperation, solidarity, sharing with, and caring for others) aiming to serve the collective interest and to increase social value and wealth. Yet, the literature that explores the links between social and solidarity economy, sustainable development and circular economy remains limited. Aiming to contribute to this literature and to advance the social dimension of CE, the current work analyzes and evaluates specific CE initiatives specialized in the reuse of used clothing in Greece, employing the perspective of social and solidarity economy. These are: a collectivity, a social enterprise, and a non-profit organization. The research assesses their effectiveness and longevity discussing also their attachment to the ideals of social and solidarity economy. It finds that the examined initiatives are all successful and satisfy to a certain degree the values and principles of social and solidarity economy, providing a sound basis to expand and enrich the concept and the approach of circular economy with due emphasis on the social dimension. Keywords: Circular economy, social and solidarity economy, reuse, second-hand clothing, sustainable development JEL codes: B52, B55, D02, L31, O17, O35, Q56